Production and antioxidant activities of Exopolymeric substances from phototrophic purple non-sulfur bacteria Rhodopseudomonas palustris PP803 - Nunkaew, Tomorn; Kaewmeesri, Putthaporn (Health Science, Science and Technology Reviews, 2020)
Purple non-sulfur photosynthetic bacteria (PNSB) is an interesting microbial group to produce exopolymeric substances (EPS). PNSB is highly productive and used a variety of carbon sources. However, the optimum culture conditions for EPS production are still less studied. In addition, the EPS has been used more in medical applications. Thus, this research aims to study the optimum conditions for EPS production from Rhodopseudomonas palustris PP803 and the EPS potential to reduce the effects of free radical activity. According to Central Composite Design (CCD) were revealed 7.82 g/L of acetate, 1.49 g/L of NaCl, and 62.83 hours of culture time result to gain the highest EPS yield (0.93) and show the highest concentration of NaCl influence from the EPS production of PP803.The antioxidant test showed that EPS at a concentration of 4 mg/mL had a Fe2+ chelating activity of 73.10% in vitro, which may be due to a group of functions. The carboxyl group in EPS structure may result in high metal chelating activity indicated that it is a good antioxidant potential. Therefore, it is a way to develop health products that have the ability to against free radicals in the future.